Efficient weighted multiselection in parallel architectures - Hong Shen (Algorithms and Architectures For Parallel Processing (ICA3PP 2002): 5th International Conference, 2002)
We study parallel solutions to the problem of weighted multiselection to select r elements on given weighted-ranks from a set S of n weighted elements, where an element is on weighted rank k if it is the smallest element such that the aggregated weight of all elements not greater than it in S is not smaller than k. We propose efficient algorithms on two of the most popular parallel architectures, hypercube and mesh. For a hypercube with p < n processors, we present a parallel algorithm running in 0(n/sup /spl isin// min{r, log p}) time for p = n/sup 1-/spl isin//, 0 < /spl isin/ < 1, which is cost optimal when r /spl ges/ p. Our algorithm on /spl radic/p /spl times/ /spl radic/p- mesh runs in O(/spl radic/p + /sub p/-/sup n/ log/sup 3/ p) time which is the same as multiselection on mesh when r /spl ges/ logp, and thus has the same optimality as multiselection in this case.